The Wizard of Oz - LeRoy, Mervyn (MGM/UA Home Video, 1991)
Transported to the land of Oz by a tornado, Dorothy journeys along the yellow brick road with her friends, the scarecrow, the tin woodman and the cowardly lion to ask help from wizard with their problems.